👤

.Sa se calculeze
1) (x + 2)² =
5) (2x - 3)² =
9) (3x - 2)² =
13) (4x + 3)² =
17) (10x + 3)² =
21) (2 - x)² =
25) (11-x)² =
29) (5-7x)²
33) (2x - 4,2)² =
37) (3,4 + x)² =
41) (x+√√2) =
www
=
3) (x + 3)²
7) (3x + 5)2 =
11) (3x - 1)²
15) (6x - 5)2 =
19) (7x-2)² =
23) (5-8x)² =
66) (x-2)(x+2) =
69) (x+4)(x-4)=
72) (4x-3)(4x+3) =
75) (6x-5);(6x+5) =
78) (7x-1):(7x+1) =
81) (3x-2)(3x+2) =
84) (6–5x);(6+5x) =
87) (11x-3)(11x+3) =
90) (8-7x)(8+7x) =
93) (8x-7)(8x+7)=
2) (x - 1)² =
6) (2x + 1)² =
10) (4x - 1)² =
14) (x + 6)² =
18)(5x + 1)2 =
22) (5-2x)² =
26) (6-4x)² =
30) (1 12x)2 =
34) (3x 1,6)² =
38) (6,1 – 5x)2 =
42)(x-√3)= 43) (x√2-3)² = 44) (√2x − 1)² =
27) (3-7x)² =
31) (1,3-x)² =
35) (2,6 + 3x)² =
39) (7x-2,3)² =
4) (x-4)² =
8) (2x-7)² =
67) (2x-1) (2x+1)=
70) (3x+4) (3x-4)=
73) (9x+4) (9x-4) =
76) (12x+1) (12x-1)=
79) (15x+8) (15x-8)=
82) (4x-1) (4x+1)=
85) (7-4x) (7+4x)=
88) (16x+3) (16x-3) =
91) (3-10x) (3+10x) =
94) (20x-7) (20x+7)=
12) (2x + 5)² =
16) (8x + 3)² =
20) (5x – 3)2 =
24) (9-2x)2 =
28) (2 - 9x)² =
32) (1,8x + 1)² =
36) (7,2 + 2x)² =
40) (6x-4,5)² =
68) (8x-3) (8x+3) =
71)(5x+2)(5x−2)=
74) (10x+7) (10x-7)=
77) (14x-3) (14x+3) =
80) (13x-5) (13x+5) =
83) (5-2x) (5+2x) =
86) (4-9x) (4+9x) =
89) (9–5x):(9+5x)=
92) (7x-5) (7x+5) =
95) (17x-3) (17+3) =